Features of the immune status in patients with chronic and complicated pyodermas: choice of a therapeutic correction method - Roman A. Khmel'nitskij; Andrej V. Vislobokov; Pavel V. Kalutskii (Belgorod National Research University, 2021)
Introduction: To compare the features of the immune status in patients with chronic and complicated pyoderma in the course of complex pharmacotherapy using immunomodulators based on transfer factors and glucosaminylmuramyldipeptide. Materials and methods: A clinical examination of 107 patients with pyoderma, divided into three groups, was carried out. All individuals underwent immunological examination before and after etiopathogenetic treatment. The patients of the first group were additionally treated with a drug containing signaling immunoactive molecules (transfer factor) as an immunomodulator; the patients of the second group received glucosaminylmuramyldipeptide; and the patients of the third group received standard antibacterial therapy. Results and discussion: Prior to the beginning of pathogenetic therapy, the patients were found to lack non-specific mechanisms of antimicrobial protection; there was a decrease in the activity and intensity of phagocytosis: phagocytic index and phagocytic number of neutrophils by 1.2 and 1.3 times; the production of proinflammatory cytokines IL-6 increased by 2.3 times, IL-8 -by 2.1 times, and TNFa - by 2.4 times. The study of immunological parameters after the inclusion of immunomodulators into the therapy revealed an increase in the phagocytic activity of neutrophils, and the indicators of the NST test were close to the control ones. The production of proinflammatory cytokines in the blood serum was restored to the level of the healthy individuals. Normalization of the number of CD4+-, CD8+-, CD19+-cells was observed in 86.0 ± 3% of the patients. At the same time, against the background of the use of glucosaminylmuramyldipeptide, a more intensive recovery of all links of anti-infectious immunity was recorded in comparison with the group where transfer factor molecules were used. Conclusion: A drug based on glucosaminylmuramyldipeptide can be recommended as the drug of choice in non-specific immunocorrection for complex pharmacotherapy of pyoderma accompanied by secondary immune insufficiency, in comparison with a drug containing transfer factors.